The Strategy of Bojonegoro University Library Facing the Era of Society 5.0 by Implementing the Internet of Things (IoT) in Library Services - Ariyanti, Novi Nur; Zulaikha, Sri Rohyanti (Universitas Wijaya Kusuma Surabaya, 2024)
The Society 5.0 era is divided into Big data, the Internet of Things (IoT), and Artificial Intelligence (AI). Purpose Research implementation of the Internet of Things (IoT) in library services to face the era of society 5.0 Research Method: Descriptive qualitative research, determining informants using purposive sampling. Data analysis using the triangulation method, namely data obtained from direct observation, interviews, and personal documentation, the Bojonegoro University Library as a place for observation. Results: The results of research on the application of the Internet of Things (IoT) to library services have advantages that can provide optimal and efficient services Keywords: Internet of Things (IoT), Era Society 5.0, Library Services